(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تناول هذا البحث الواقع السكاني وتحليل السياسة السكانية المتبعة في سورية ودراسة كفاءتها وأثرها على المؤشرات الديموغرافية كافة وأهمية وضع سياسة سكانية معلنة ومتبناة رسميا" من كل الجهات والمؤسسات الحكومية والمنظمات الشعبية ومنظمات المجتمع الأهلي والمنظمات الدولية, وأن يكون الهدف الرئيس للسياسة السكانية في سورية تحقيق المواءمة بين النمو السكاني والنمو الاقتصادي والاجتماعي لتلبية المتطلبات المتنامية للسكان لخدمات التعليم والصحة والمياه والكهرباء والمواصلات والبطالة وغيرها من الاحتياجات التي ترفع من المستوى المعيشي للسكان وتأمين مستوى الرفاه حيث شملت الأهداف الإستراتيجية للسياسة السكانية مجالات النمو السكاني والصحة الإنجابية وتمكين المرأة والشباب والمشاركة المجتمعية والعمل والتعليم والتوزع الجغرافي للسكان والتمدين والاستفادة من احتمال انفتاح النافذة الديموغرافية والإعلام وتنمية الوعي بقضايا السكان كما تضمنت أسس السياسة السكانية ومستلزماتها على المستوى التشريعي والقانوني والمؤسساتي الحكومي الأهلي والإعلامي والتعليمي والصحي والاقتصادي والبيانات والمعلومات وتحديثها. يجب أن تكون هذه السياسة تدخلية تذلل العقبات وتستثمر الفرص وتدمج البعد السكاني بالأبعاد التنموية المختلفة وتنفيذها دون أن تبقى حبرا" على ورق . This research tries to go into the demographic reality and analysis of population policy followed in Syria, and study their efficiency and their impact on demographic indicators all and the importance of developing a population policy declared and espoused officially "from all sides, government institutions and people’s organizations, civil society organizations and international organizations, and that the main objective of the population policy in Syria to achieve harmonization between population growth and economic and social development to meet the growing needs of the population to education and health services, water, electricity, transportation, unemployment and other needs, which raises the standard of living of the population and provide the level of well-being which included the strategic objectives of population policy areas of population growth and reproductive health and empowerment of women, youth and community participation, employment, education and geographical distribution the urbanization of the population and take advantage of the possibility of opening up the window of demographic, media, and develop an awareness of population issues also included the foundations of population policy and accessories at the legislative level, and the legal and institutional framework of civil government, media and educational, health and economic data, information and updated. Should be this policy intrusive overcome obstacles and investing opportunities and integrate the population dimension dimensions of the various development and implementation without the remaining ink "on paper.